Pengaruh Kepemimpinan dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Pendidikan Kota Banjarmasin - Amalia, Eva; Rudiansyah, Muhammad (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
This study aims to determine the effect of leadership and work discipline partially, and the effect of leadership and work discipline simultaneously on employee performance at Dinas Pendidikan Kota Banjarmasin.This research uses quantitative methods. The data used in this study consisted of primary data and secondary data. The population of this research is the employees of Dinas Pendidikan Kota Banjarmasin, amounting to 102 people. Sampling uses probability sampling. The technique of data collection was carried out by distributing questionnaires to 51 respondents from Dinas Pendidikan Kota Banjarmasin employees who were obtained using the Slovin formula. The data analysis technique used is multiple linear regression to determine the effect of leadership and work discipline on performance in Dinas Pendidikan Kota Banjarmasin using Statistical Package for the Social Science (SPSS) version 21.00 for windows.The results of the study concluded that the leadership and work discipline variables partially affect the performance of employees at the Banjarmasin City Education Office. The results of the study concluded that the variables of leadership and work discipline simultaneously affect the performance of employees at Dinas Pendidikan Kota Banjarmasin.